Penguatan edu-Green Entrepreneurship melalui Pengembangan Leaflet Projek Rezin Blok dalam Pengolahan Limbah di MA Da'watul Khoir Nganjuk - Meishanti, Ospa Pea Yuanita; Sholihah, Fatikhatun Nikmatus (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
ABSTRACT Important problems that are currently of concern are threats to the environment, including depletion of the ozone layer, global warming, pollution of water, land, air and flooding, so that various efforts are made, among others, by creating a sense of belonging to nature and being environmentally friendly. waste processing and green economy. . The aim of the research is to describe the suitability of the material, media and response to the attractiveness of the leaflet. The research method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation) by conducting feasibility tests on materials, media for experts and the attractiveness of leaflet media. The development results obtained from expert validation of leaflet media material showed a percentage of 90% with very appropriate eligibility criteria, so that leaflets were effectively used as teaching materials. The media feasibility results were 90% with very feasible eligibility criteria. The attractiveness of leaflet products is 83% with very attractive criteria. So leaflet media is suitable for use as learning media because it can improve student learning outcomes. KEYWORDS: edu-Green Entrepreneurship Leaflet Block Rezin Project in Waste Processing ABSTRAK Isu penting saat ini yang menjadi perhatian yakni tentang ancaman mengenai lingkungan hidup antara lain penipisan lapisan ozon, global warming, pencemaran air, tanah, udara dan banjir, sehingga berbagai upaya sedang diterapkan antara memunculkan rasa memiliki tentang alam, pengolahan limbah ramah lingkungan serta green economy. Tujuan penelitian mendeskripsikan kelayakan materi, media dan respon kemenarikan leafled. Metode penelitian yakni ADDIE (Analysis, Desain, Development, Implementasi, Evaluation) dengan melaksanakan uji kelayakan materi, media kepada ahli dan kemenarikan media leaflet. Hasil pengembangan diperoleh Hasil validasi ahli materi media leafled diperoleh presentase sebesar 90% dengan kriteria kelayakan sangat layak, sehingga leaflet efektif digunakan sebagai bahan ajar. Hasil kelayakan media sebesar 90% dengan kriteria kelayakan sangat layak. Kemenarikan produk leaflet sebesar 83% dengan kriteria sangat menarik. Sehingga media leaflet layak dijadikan sebagai media pembelajaran karena dapat meningkatkan hasil belajar siswa. KATA KUNCI : edu-Green Entrepreneurship, Leaflet, Block Rezin, Limbah